Are female directors more employee-friendly? Board gender diversity and employee benefits: evidence from China - Liu, Yao; Tang, Yingkai; Yang, Yunfan (Frontiers in Psychology, 2024)
The imperative of gender diversity in corporate governance and the adoption of a human-centric governance paradigm are intensifying globally. The structure of board directors, key influencers to corporate decisions, notably shape policies, crucially in emerging markets like China where gender issues are still evolving. Therefore, employing a penal dataset comprising 8,973 firm-year observations from publicly A-share-listed Chinese firms spanning 2006 to 2021, this study empirically examines the impact of board gender diversity on the responsiveness to both employee monetary incentives and non-monetary rewards. The findings unveil a positive correlation, indicating an augmentation in peremployee compensation and an increased likelihood of implementing non-monetary programs, including stock-ownership plans, retirement benefits, and occupational safety certification, in the presence of higher board gender diversity. Notably, these positive associations are more accentuated in state-owned firms, as well as those with lower executive compensation and diminished institutional ownership. Our results remain consistent after considering robustness as well as endogeneity. This empirical evidence not only contributes robust statistical support to the ongoing global initiatives advocating for gender diversity in corporate governance but also underscores the efficacy of boards of directors in effectively managing stakeholder interests, particularly in fostering employee-friendly practices within emerging markets like China.